Mathematical modeling and simulation for external electrothermal characteristics of an alkaline water electrolyzer. (21st June 2018) - Shen, Xiaojun; Zhang, Xiaoyun; Lie, Tek Tjing; Li, Guojie
Summary: The water electrolyzer is a key device in the direct energy interaction between the hydrogen production system and the fluctuation power supply. Therefore, to understand its external electrothermal characteristics and modeling, an efficient simulation method is not only theoretically significant but also of great value in engineering applications for the key techniques, such as the study of control strategy and optimum configuration of renewable energy generation. Currently, research studies on the electrothermal characteristics of the alkaline water electrolyzer (AWE) are focused mainly on the microcosmic mechanism, without sufficient emphasis on the modeling and simulation technique of the external macroscopic electrothermal characteristics. Based on relevant theories in electrochemistry and test results of the electrothermal characteristics, this paper establishes a mathematical model of the equivalent impedance characteristics, electrothermal characteristics, and power regulation characteristics of AWE. Then, a simulation model of the external electrothermal characteristics is built with Matlab/Simulink. Finally, the accuracy of the established mathematical model and the functionality of the simulation model are verified. The research can provide some reference for the modeling and simulation of the electrical characteristics of AWE. Abstract : Established a mathematical model of the external characteristics of AWE with temperature as a variable. An external electrothermal simulation model was built on the basis of Matlab/Simulink. The established simulation model can be used to simulate the external characteristics and the quantitative relationship among the electrolyzer's working temperature, thermal power, and ambient temperature by changing various parameters.